HUBUNGAN PERSEPSI PRAKTIK PENGASUHAN ORANG TUA DAN ADAPTASI MAHASISWA INDONESIA DI AMERIKA - Catherina Kartika Hapsari; Yapina Widyawati (Provitae: Jurnal Psikologi Pendidikan, 2016)
Currently the number of Indonesian students study abroad is increasing, especially in the United States. American study program is different with Indonesian, include distance, time differences, and also American culture. This situation could cause a problem in adjustment, language and culture. Parents need to pay more attention to their role in adolescent adaptation. Parenting practices can have a direct impact on child's behavior. Another factor is the proximity and discipline from their parents so that children can master the competencies and self-regulation. This study aims to determine the relationship perceptions of parenting practices with the adaptation of Indonesian students in the United States. Researchers used the test tool Adaptation College Student Questionnaire (SACQ) to measure the level of adaptation. Perception of parenting practices on adolescent developed by Baker and Siryk (in Waller, 2009). The study involved 57 Indonesian students currently studying in the United States. The results indicate perceptions of parenting did not have a significant relationship with the adaptation of Indonesian students in the United States. The adaptation rate of Indonesian students tends to be high. The perceived level of parental practices on the students tends to be in the moderate level although there are different parenting factors. There was a significant relationship between perception of parenting practices of the father with social adaptation and adaptation of the students.Keywords : Parenting, Student adaptation